1988
DOI: 10.1128/iai.56.3.552-556.1988
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial mechanisms against Acinetobacter calcoaceticus of rat polymorphonuclear leukocyte granule extract

Abstract: The antimicrobial mechanisms of rat polymorphonuclear leukocyte granule extract and isolated extract fractions against Acinetobacter calcoaceticus were examined. Crude granule extract and a fraction containing low-molecular-weight cationic peptides (peak D) reduced the viability of A. calcoaceticus and inhibited the uptake of radiolabeled macromolecule precursors by cells. The inhibitory activity observed with peak D was not as great as that of crude granule extract containing equivalent amounts of peak D prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…These included S. aureus 502A, two gram-negative bacteria, two fungi, and, to a lesser extent, an enveloped virus. Because we purified RatNP-1, -3, and -4 to homogeneity and we used different microbial targets and assay conditions, it is not possible to compare our studies directly with those of Modrzakowski et al (17,18,25,28). Nevertheless, our data confirm their report that cationic, lowmolecular-weight antimicrobial peptides exist in rat PMN.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These included S. aureus 502A, two gram-negative bacteria, two fungi, and, to a lesser extent, an enveloped virus. Because we purified RatNP-1, -3, and -4 to homogeneity and we used different microbial targets and assay conditions, it is not possible to compare our studies directly with those of Modrzakowski et al (17,18,25,28). Nevertheless, our data confirm their report that cationic, lowmolecular-weight antimicrobial peptides exist in rat PMN.…”
Section: Discussionsupporting
confidence: 69%
“…Although defensins have not heretofore been described in rat PMN, Modrzakowski et al reported that an extract prepared from rat PMN exerted antibacterial activity against certain bacteria (17,18,24,25,28), and they associated the activity of these extracts with small cationic peptides. Because rats are widely used in experimental models of infection, precise characterization of their antimicrobial effector molecules is desirable.…”
mentioning
confidence: 99%
“…Clinical studies have shown that A. baumannii is one of the most frequently isolated gram-negative bacteria in neutropenic febrile patients in nosocomial settings, ( Karim et al, 1991 ; Fukuta et al, 2013 ; Yadegarynia et al, 2013 ; Kim et al, 2014 ) particularly after prolonged hospitalization ( Wisplinghoff et al, 2004 ). Previous studies have also shown that neutrophils ( van Faassen et al, 2007 ; Qiu et al, 2009 ) and neutrophil-recruiting chemokines ( Zhao et al, 2011 ) are present at the site of A. baumannii infection, and neutrophil granule extract is bactericidal to other species of Acinetobacter ( Loeffelholz and Modrzakowski, 1988 ). However, the contribution of neutrophils in host resistance to cutaneous A. baumannii infection has not been directly investigated.…”
Section: Introductionmentioning
confidence: 99%